The Hypolipidemic Property of Pomelo Fruit Extract on Sprague-Dawley Rats - Viloria, Evony; Tuazon, Jeric; Lomibao, Gloryfe; Pamilaran, John Earl; Manaig, Crismiel Anne (International Journal of Sustainability and Advanced Integrated Research, 2026)
This study evaluated the hypolipidemic activity of ethanolic pomelo (Citrus maxima [Burm.] Merr.) fruit extract in male Sprague-Dawley rats exposed to a high-fat diet. Guided by a bioactive-compound–lipid-regulation framework, the study examined whether the extract’s phytochemical constituents could influence total cholesterol, triglycerides, high-density lipoprotein, low-density lipoprotein, and very-low-density lipoprotein. A randomized experimental design was employed using 15 rats assigned to pomelo-extract, positive-control, and negative-control groups, with five animals per group. The treatment group received 150 mg/kg body weight of the extract. Qualitative phytochemical screening and laboratory lipid-profile testing were conducted, while the data were analyzed using descriptive statistics, one-way analysis of variance, post hoc comparison, and the Kruskal–Wallis test. Flavonoids and coumarins were detected in the extract, whereas anthocyanins, phenols, saponins, steroids, tannins, and terpenoids were not detected. Compared with the untreated group, the pomelo-treated group had lower total cholesterol and LDL concentrations. The treated group also recorded the highest mean HDL concentration, although the reported HDL probability value and the stated significance threshold require clarification. No significant differences were observed in triglyceride and VLDL levels. The findings indicate that the extract demonstrated selective cholesterol-modulating activity rather than a uniform effect on the entire lipid profile. Further studies should use larger samples, multiple doses, longer treatment periods, quantitative phytochemical analysis, toxicity assessment, and pre- and post-treatment measurements. The research supports SDG 3 by contributing preliminary evidence related to cardiovascular-risk reduction and SDG 9 by promoting laboratory-based natural-product innovation. Its sustainability contribution lies in supporting public health research and the potential value-added use of a locally available agricultural resource, subject to further validation.